Definition of an HBsAg to DNA international unit conversion factor by enrichment of circulating hepatitis B virus forms. Issue 9 (29th January 2015) - Désiré, N.; Ngo, Y.; Franetich, J.‐F.; Dembele, L.; Mazier, D.; Vaillant, J.‐C.; Poynard, T.; Thibault, V.
Summary Hepatitis B (HBV) virus infection is characterized by the overproduction of subviral particles (SVP) over infectious Dane particles (VP). Precise regulation of the ratio between these forms is unknown, but its fluctuation may have a clinical impact. An enrichment method was applied to assess the SVP/VP ratio in chronically infected patients (CHB) and to compare the sensitivity of HBs antigen (HBsAg) and DNA detection methods. Plasmas from 9 genotype A–D CHB patients were fractionated on Nycodenz® gradients, and both HBV DNA and HBsAg were quantified in each collected fraction using standardized techniques expressed in IU/mL. Infection of primary human hepatocytes (PHHs) was performed with crude or fractionated plasma. Independently of the genotype, all plasmas showed a similar rate‐zonal separation profile characterized by a bottom DNA‐enriched peak surmounted by HBsAg‐enriched fractions. Inoculation of PHH with plasma‐derived VP‐enriched fractions led to long‐lasting production of virus in cell supernatants with a SVP/VP ratio similar to that observed in patient plasmas. In the VP fraction, one IU of HBsAg corresponded to approximately 5 million IU of HBV DNA. Rate‐zonal gradient separation directly applied on patient plasma allows a better insight into the distribution of VP in HBeAg‐positive CHB carriers. This study highlights the sensitivity difference of the techniques classically used to monitor HBV infection and indicates that VP‐associated HBsAg contributes modestly to the overall amount of total circulating HBsAg in CHB. Such a fractionation approach should help to understand the fine regulation of HBsAg production over replication at different stages of CHB.